2019
DOI: 10.3889/oamjms.2019.051
|View full text |Cite
|
Sign up to set email alerts
|

Using Patch Testing to Improve Therapeutic Outcome in the Treatment of Hand Eczema in Vietnamese Patients

Abstract: BACKGROUND:Hand eczema is a common chronic and relapsing skin disease with various clinical features. Hand eczema aetiology can be allergic contact dermatitis (ACD), irritant contact dermatitis (ICD), atopic dermatitis (AD) and unknown or combination causes. If the causative agents are not detected treatment of hand eczema will be a failure. A patch test can be useful to detect causative agents in suspected allergic contact hand eczema. Then patients will avoid contacting them. This results in the improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…16,22,35,49 In 2 studies, patch testing was reported to have clinical relevance of 78% in P-CHE and 76.2% in pediatric hand eczema, 22,50 which was much higher than that reported in adult studies. 51,52 The literature has not supported immunoglobulin E testing because no association has been found between positive specific immunoglobulin E during childhood and P-CHE. 17 The use of standardized severity assessments is rare in the P-CHE literature, with one P-CHE study using the Hand Eczema Severity Index and Investigator Global Assessment 24 and one study using the Hand Eczema Extent Score.…”
Section: Risk Factors and Diagnosesmentioning
confidence: 99%
“…16,22,35,49 In 2 studies, patch testing was reported to have clinical relevance of 78% in P-CHE and 76.2% in pediatric hand eczema, 22,50 which was much higher than that reported in adult studies. 51,52 The literature has not supported immunoglobulin E testing because no association has been found between positive specific immunoglobulin E during childhood and P-CHE. 17 The use of standardized severity assessments is rare in the P-CHE literature, with one P-CHE study using the Hand Eczema Severity Index and Investigator Global Assessment 24 and one study using the Hand Eczema Extent Score.…”
Section: Risk Factors and Diagnosesmentioning
confidence: 99%